Factors affecting quality of life in adults with HIV: A local cross-sectional study - Karina Berner; Quinette A. Louw (AOSIS, 2023)
Background: Understanding health-related quality of life (HRQOL) among people with HIV (PWH) can inform strategies to maintain or improve health and functioning. Most HRQOL research has focused on resource-rich settings, underrepresenting younger cohorts in low-resource settings. Objectives: To assess HRQOL and associated factors in PWH visiting two primary healthcare clinics in the Western Cape, South Africa. Method: A cross-sectional study included 48 PWH (58.3% women; mean age: 39.2 [10.3]). Health-related QOL was assessed using EQ-5D-5L descriptive domains, visual analogue scale (EQ-VAS), and index score (EQ-index). Mobility was assessed using clinical tests. Tobit regression determined associations. Results: Mean and median EQ-VAS scores were 88.14 (16.35) and 95.00. Mean and median EQ-index scores were 0.84 (0.10) and 0.90. PWH reported problems as pain/discomfort (35.4%), depression/anxiety (25.0%), mobility (22.9%), usual activities (18.7%) and self-care (12.5%) domains. Slow chair rise (p = 0.012), low income (p = 0.030), longer HIV duration (p = 0.009) and polypharmacy (p = 0.034) were associated with lower HRQOL. Antiretroviral therapy (ART) adherence was associated with higher HRQOL (p = 0.020). Conclusion: Despite high overall HRQOL, specific domains presented challenges to PWH. Health-related QOL was associated with chair rise repetitions, income, HIV duration, polypharmacy, and treatment adherence. Comprehensive care and contextualised interventions to address these through rehabilitation, including health promotion, are proposed strategies for future investigation. Clinical implications: Clinicians should be cognisant of potential physical and mental functioning problems, and factors related to drug therapy, socio-economic status and disease duration that may affect HRQOL even in seemingly unimpaired PWH.